Electrical and Mechanical Properties Enhancement in Superlattice‐Like GaSb/Ge2Sb2Te5 Phase Change Thin Films. Issue 14 (17th June 2021) - Yin, Qixun; Wang, Ming; Xu, Xiulan; Yu, Guanghua; Chen, Leng
Abstract: A promising phase change materials based on a distinct nanoscale structure called superlattice is applied in lateral phase change memory (PCM) due to comprehensive performances. In this work, superlattice‐like structure of [GaSb( x )/Ge2 Sb2 Te5 ( y )] n ( x  = 6, 9, 12, 18 nm; y  = 12, 18 nm; n  = 3, 6) thin films is proposed and alternatively deposited with GaSb and Ge2 Sb2 Te5 (GST) layers by magnetron sputtering method. The experimental results show that [GaSb( x nm)/GST(12 nm)]3 thin films possess higher crystallization temperature and less volume change than that of monolayer GST. Moreover, [GaSb( x )/GST(12)]3 thin films show super‐hardness and super‐modulus effect. The hardness enhancement mechanism is discussed and the critical thickness of GST layer is calculated as ≈18.1 nm, thus the interfaces are coherent without dislocation threading in critical condition. Therefore, the higher thermal stability and increased hardness values reflect great potential in practical application of superlattice‐like [GaSb( x )/GST(12)] n thin films. Abstract : The superlattice‐like structure of [GaSb( x nm)/Ge2 Sb2 Te5 (GST) (12 nm)]3 thin films is proposed. The performance of [GaSb( x nm)/GST(12 nm)]3 thin films with less volume change (0.7%), higher crystallization temperature, and super‐hardness and super‐modulus effect than that of monolayer GST is proved.